Muon g − 2 and non-thermal leptogenesis in U 1 L μ − L τ $$ U{(1)}_{L_{μ }-L_{τ }} $$ model - Shintaro Eijima; Masahiro Ibe; Kai Murai (Journal of High Energy Physics, 2023)
Abstract The gauged U 1 L μ − L τ $$ U{(1)}_{L_{μ }-L_{τ }} $$ symmetry is the simplest possibility to explain the observed muon g − 2, while being consistent with the neutrino oscillations through the seesaw mechanism. In this paper, we investigate if leptogenesis can work at the same time. At first glance, leptogenesis seems challenging because the right-handed neutrino masses are related to the U 1 L μ − L τ $$ U{(1)}_{L_{μ }-L_{τ }} $$ breaking scale of 10 – 100 GeV as required from the muon g − 2. Contrary to this expectation, we find that non-thermal leptogenesis with the right-handed neutrino masses of O $$ \mathcal{O} $$ (107) GeV is possible. The successful scenario results in strict predictions on the neutrino oscillation parameters, which will be tested in future experiments.